Laterally coupled distributed feedback cascade diode lasers emitting near 2.9 µm. Issue 10 (1st May 2016) - Hosoda, T.; Fradet, M.; Frez, C.; Shterengas, L.; Sander, S.; Forouhar, S.; Belenky, G.
Abstract : Cascade type‐I quantum well GaSb‐based laterally coupled distributed feedback diode lasers emitting near 2.9 µm were designed and fabricated. Second order index grating with period of 825 nm was defined by e‐beam lithography and etched on both sides of 4‐µm‐wide shallow ridge waveguide. Anti‐/neutral reflection coated 2‐mm‐long devices that were solder‐mounted epitaxial side‐up demonstrated stable single frequency operation in a wide temperature range with output power of 13 mW at 20°C. Bragg wavelength temperature tuning rate was ∼0.32 nm/K.